Students' Perceptions of Zoom Video Conferencing Platform During the Covid-19 Pandemic: A Case of Malaysian University - Alia, Nur Natasha; Antasya, Nur Aslinda; Aireen, Nur Elysha; Amy, Nur Nazira; Malthane, Bhushan Rameshwar (AIBPM Publisher, 2022)
Since the covid-19 pandemic has been a hazardous situation in the world, the physical class has been forced to shift towards online teaching and learning in universities worldwide. Zoom has been used extensively during the pandemic to facilitate students' learning process. This paper studied students' perceptions of Zoom during the pandemic as a platform for the learning process. A total of 100 local students from Malaysian universities participated in the study. From this analysis, students perceived Zoom as an Open and Distance Learning (ODL) platform during Covid-19. The finding shows that Zoom has its own weakness, such as limited participants and features for the users. Therefore, the method of online learning needs to be improved too. Both the study management and Zoom company could be improved in which the universities could manage limited face-to-face classes while the Zoom company could make more participants and longer the discussing time.